(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This article has no abstract. The first 100 words appear below: A 42 year old female presented with the complaints of thermal sensitivity and impaction of food during mastication on her lower left posterior region. On clinical examination, carious lesions involving proximal surface was detected at the lower left first molar tooth which extended up to the dentin. The vitality test showed that the affected tooth was vital and the tooth was also non-tender to percussion.